Keefektifan Konseling Kelompok Cognitive Behavioral Therapy (CBT) dengan Teknik Modeling Simbolis dan Role Playing untuk Meningkatkan Self-Confidence pada Siswa - Betsi Siti Nurhidayah; Mungin Eddy Wibowo; Edy Purwanto (Bulletin of Counseling and Psychotherapy, 2022)
Self-Confidence is a person's belief in all aspects of the advantages he has and that belief makes him feel able to achieve various goals in his life. This study aims to examine the effectiveness of CBT group counseling with symbolic modeling techniques and role play techniques on increasing students' self-confidence. This study used a pretest and multiple posttest designs. Purposive sampling technique was used to select 21 experimental subjects who were placed into three groups randomly so that each group consisted of seven students. The results of the mixed repeated measure ANOVA test showed that the CBT group counseling with symbolic modeling and role play techniques was effective in increasing students' self-confidence. This study found that the combination of symbolic modeling techniques and role play techniques shows interesting implications, so the implications of using this combination of techniques in group counseling practice are recommended in the implementation of CBT counseling.